Upaya Peningkatan Penguasaan Kosakata Kelas 1 Sekolah Dasar Melalui Papan Flanel Kata Pada Pembelajaran Bahasa Indonesia Materi Keinginan Dan Kebutuhan - M. Reza Azwaldi Zhanni; Donna Boedi Maritasari; Hurun in; M. Syahruddin Amin (EDUKASI, 2025)
Learning media is a tool to increase interest, stimulate skills, facilitate, remember and understand the information contained and motivate learning. The use of media is very important in the learning process. The aim of this research is to determine the use of word flannel board media to improve mastery of Indonesian vocabulary and maximize students' reading ability in class I of SD Negeri 3 Sekarteja, Selong District, East Lombok Regency. The method in this research was Kemmis & McTaggart with research subjects of class I students at SD Negeri 3 Sekarteja totaling 29 people. This research was carried out in two cycles starting with learning without using word flannel board media. In the first cycle, the post test results from 29 students increased to 12 students who completed it with a percentage of 41.38. In cycle II the number of results increased to 23 students with a percentage of 79.31%. The results of the research show that the use of flannel word board media is very effective in learning Indonesian, because it can improve students' vocabulary mastery skills in beginning reading.